Improving Concentration through Sensory Play in 5–6-Year-Old Children at PAUD Permata Ibu - Putri Lestari, Larasati Wisnu; Putri, Ratu Rahmawati; Rachmi, Titi (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
This classroom action research aimed to improve the concentration ability of 5–6-year-old children through sensory play activities at PAUD Permata Ibu. The problem addressed in this study was the low ability of children to maintain focus during learning activities. The research was conducted in two cycles: Cycle I utilized water-based media, and Cycle II used bead-based media. The research subjects consisted of 12 children in group B. Data were collected through observation, interviews, and documentation. The results showed a significant improvement in children’s concentration, increasing from an average of 66.5% in Cycle I to 95.7% in Cycle II. The study concludes that sensory play is proven to be an effective strategy to enhance concentration in early childhood, particularly when implemented gradually and in an enjoyable manner.